Clinical Experience with Secondary Endoscopic Reconstruction of Clival Defects with Extracranial Pericranial Flaps - Gode, Sercan; Lieber, Stefan; Nakassa, Ana Carolina Igami; Wang, Eric W.; Fernandez-Miranda, Juan C.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives The aim of this study is to report the clinical outcome of extracranial pericranial flaps (ePCF) used for reconstruction of clival dural defects following failure of primary repair.Design Retrospective review of skull base database.Setting Academic medical center.Participants Patients undergoing reconstruction of clival defects with ePCF following endoscopic endonasal surgery (EES).Main outcome measures Postoperative cerebrospinal fluid (CSF) leak, meningitis, and flap necrosis.Results Seven patients (five males and two females) who underwent ePCF reconstruction for clival defects following EES were included. All patients (ages 8–64 years) had a postoperative CSF leak due to a failed primary clival reconstruction (five had one, one had two, and one had three failed CSF leak repairs prior to ePCF reconstruction). Nasoseptal and inferior turbinate (lateral nasal wall) flaps were not available for secondary reconstruction due to prior surgeries. The immediate success rate of ePCF for the reconstruction of clival defects in patients with multiple flap failures was 58%. Two patients developed CSF leaks that were successfully repaired endoscopically with the addition of free tissue grafts; one patient had partial flap necrosis that required debridement; none required an additional vascularized flap. Width of the defect, length of the defect, properties of the ePCF, and age did not demonstrate significance (p > 0.05) for adverse outcome.Conclusion An ePCF is a reconstructive option for high-risk, large clival defects when other local and regional vascularized flaps are not available or fail. ePCFs can be used for reconstruction of clival defects in all populations, including pediatric patients.
Keywords: chordoma; clival defect; pericranial flap; skull base reconstruction; skull base tumors